Analysis of The Effect Of Financial Distress Conditions On Activity / Efficiency Ratios In Manufacturing Companies In Indonesian Stock Exchange During The Covid Period - Yacobus, Aryono; KP, Hasa Nurrohim (RSF Conference Series: Business, Management and Social Sciences, 2021)
The study aims to retest the financial ratios derived from balance sheets, income statements, and cash flow statements. This research is also to find out the effect of financial distress conditions on the activities of companies in the manufacturing industry sector during the Covid period. Is there an influence on financial to activity ratios for companies experiencing financial distress during the covid period?. This study used logistical statistical analysis while to determine whether the company experienced financial distress or not, using Altman’s Z Score value analysis. After testing, it was found that the ratio of cash position and activity ratio had a significant effect on companies experiencing financial distress.